Review On “Panchakarmam Athava Sodhanachikitsa” - Nair, Prathibha S; Jigeesh , P P (International Research Journal of Ayurveda & Yoga, 2021)
Kerala is rightly considered as the abode of Ayurveda. That title largely owes to the contributions of old vaidyas of Kerala. They not only developed special treatment methodologies based on Ayurvedic principles, viz Shashtikapindasweda, Murdha taila kalpana etc, but also brought out numerous Ayurvedic textbooks which explains and expands on the fundamental principles of Ayurveda.